Effects of Different Management Practices on the Increase in Phytolith-Occluded Carbon in Moso Bamboo Forests - Lv, Wanjie; Zhou, Guomo; Chen, Guangsheng; Zhou, Yufeng; Ge, Zhipeng; Niu, Zhengwen; Xu, Lin; Shi, Yongjun (Frontiers in Plant Science, 2020)
Phytolith-occluded carbon (PhytOC), one of the most promising biogeochemical carbon sequestration mechanisms, plays a crucial role in the global carbon cycle and the regulation of atmospheric CO2. Previous studies focused on the content and storage estimation of PhytOC, while it still remains unclear on how the management measures affect the PhytOC content and whether it varied with age. Moso bamboo (Phyllostachys heterocycla var.pubescens) is one of the plants rich in PhytOC. Therefore, we selected four management measures, including control, compound fertilization, Si fertilization and cut to investigate the variation of phytoliths and PhytOC content in soil, leaves and litterfall, and their storage in Moso bamboo forests. For soil, the effects of Si fertilizer were significant in phytolith content, PhytOC content and PhytOC storage (p<0.05). While there were no significant differences in compound fertilizer and cut measures. For leaf, phytolith content of the second-degree leaves under Si fertilization and the first-degree leaves under the cut treatment reached a significant level (p<0.05). Almost all its PhytOC storage have reached significant levels (p<0.05). Among them, the second- and third-degree leaves under Si fertilizer and the first-degree leaves under compound fertilizer reached the maximum value, 72.5%, 45.4%, and 41.7%, respectively. For litterfall, phytolith content and PhytOC content increased, but did not reach a significant level, the PhytOC storage was increased by 19.33% under Si fertilization, but decreased by 40.63% under compound fertilization and 20.25% under the cut treatment, and had reached a significant level (p<0.05) under compound fertilizer. For Moso bamboo forest ecosystems, the PhytOC storage of all the three management measures had a varying degree increase compared with control groups, in which the PhytOC storage had the most increase by 102% under Si fertilization. This study indicates that the effects of management measures on the accumulation of PhytOC varied with age and had produced positive feedback in PhytOC accumulating in Moso bamboo forests. Optimizing management measures is a promising approach to increase the accumulation of PhytOC in Moso bamboo forests, especially Si fertilization, which is essential to promote the capacity of sequestration carbon in Moso bamboo forests.